Improved pregnancy and birth rates with routine application of nonsurgical embryo transfer - Bin Ali, Rahmen (Springer International Publishing, 2014)
Nonsurgical embryo transfer (NSET) of blastocysts to pseudopregnant female recipients provides many benefits over surgical implantation with less distress for the mice, no anesthesia or analgesia required and a considerable reduction in implantation time per mouse. Although a disposable device to perform NSET is on the market since 2009, it is not generally used in transgenic facilities, most likely because surgical implantation is efficient and inexpensive. Here, we report that with several refinements to the original protocol, the NSET method becomes very attractive and outperforms the traditional surgical transfer on basis of pregnancy rate, birth rate and implantation-related discomfort. Furthermore, repeated use of the same NSET device on several recipient females reduces the costs to a reasonable level. The data presented covers all embryo transfers over the last 5 years at the transgenic facility of the Netherlands Cancer Institute, of which the last 2 years were performed exclusively with NSET.